Pengaruh Periklanan Televisi Dan Duta Merek Terhadap Pembentukan Kesadaran Merek Pada Tokopedia Seri Bangtan Sonyeondan - Dewi Laily Purnamasari; Aulia Dwi Septyani; Ibrahim Rasyid Ridho Rusydi (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2022)
Technological advances and the increasing needs of society make companies complete to crete good relitionships with consumers and potential counsumers as well as form brandawareness in consumers. This study aims to: 1) To determine the effect of television advertising one the formation of brand awareness in the Tokopedia Bangtan Sonyeondan series; 2)To determine the influence of brand ambassador on the formation or brand awareness in the Tokopedia Bangtan Sonyeondan series; 3) To determine the effect of television advertising and brand ambassadors on the formation of brand awareness in the Tokopedia Bangtan Sonyeondan series. This research is descriptive and verification with a sample of 100 people in the city of Cirebon aged 20-50 years form a total of 145,993 inhabitants. This data was analyzed by multiple linear regression, correlation and determination. The results showe the partially television advertising has and effect on the formation of brand awareness (sig= 0.002 0.005); brand ambassadors influence the formation of brand awareness (sig= 0.001 0.005). television advertising has a strong relationship with brand ambassadors with a correlation coefficient value of 0.657. the higher the correlation coefficient, the better the correlation model because the independent variables can explain the dependent variabel better.